Analisis Yuridis Penanganan Barang Bukti Kapal Asing Pelaku Tindak Pidana Perikanan “Illegal Fishing” - Triono Eddy; Putri Raudhatul Zannah (CV. Creative Tugu Pena, 2024)
Act of the Republic of Indonesia No. 45 of 2009 Amendment to Act of the Republic of Indonesia No. 31 of 2004 concerning Fishery regulates all activities related to the management and utilization of fish resources and the environment, starting from pre-production, production, processing, to marketing, which is carried out in a fisheries business system. Illegal Fishing is fishing without a permit, using fake permits, using prohibited fishing gear, and catching species of fish that do not comply with the permit. Destruction of evidence in the form of fishing boats with foreign flags is carried out by burning, exploding, sinking, and leaking the wall and opening the sea taps, then sinking them. The research problems in this study are: 1) What is the form of law enforcement against illegal fishing in Indonesia? 2) What is the legal system related to handling the evidence of foreign boats committing illegal fishing? 3) How can illegal fishing be eradicated in efforts to manage marine and fisheries sources in Indonesia? This study is normative legal research with a statute approach in conducting the study. The data collection techniques used were library research and interviews. Based on the results of the study, data on illegal fishing in the fishing sector handled regarding the evidence of boats being burned, sunk, and/or destroyed in Marine and Fisheries Resources Surveillance (PSDKP) of Batam City of 2022, 2023, and 2024 show that there are eighteen (18) units of boats with Malaysia, Myanmar, and Vietnam flags that have been sunk with other supporting facilities and equipment in committing illegal fishing, such as purse seine, trawl, fishing lights, hand line, GPS Samsung, HF Transceiver VX-1700, Radio Sea Eagle 6900, Compass Express, navigation and communication tool.